Evolution after 1990 of the Legal Framework with the Incidence on the Managerial Ethics of the Romanian Firms - Avram, Laurentia Georgeta (Journal of Economic Development, Environment and People, 2014)
Abstract. Firms with an ethical behaviour, which satisfy the conditions of morality, namely to respect applicable law articles, have certain characteristics: “balance between profit and ethics; ethical values underlying the daily behaviour of individual actions; penalty system which provides penalty and correction actions by unethical nature; set of values that involves treating others with respect and honesty as you want and to be treated; manufacture and marketing of the products so that you are be thankful if you use them; treating the environment as it would be your property”. In Romania, although the law has improved methodologically according to the European Directives, but problems arise in its implementation. The Commission report to the European Parliament and the Council on Progress in Romania under the Cooperation and Verification Mechanism SEC (2008) 2539 show that Romania continues to face important difficulties in the functioning of its judiciary and fighting the corruption. In 2013, the political clienteles and corruption have worsened the Romanian state budget, representing, however, the greatest threat to the economic growth (MCV Report - 2013 - Brussels, 30.01.2013 COM (2013) 47 final). What are the solutions? There are the political stability and, not least, that constitutional.